LEVEL OF CUSTOMER ORIENTATION AND CUSTOMER PROTECTION IN HOTELS IN SERBIA - Ćirić, Maja; Počuča, Milan; Raičević, Vuk (Economics of Agriculture, 2014)
Hotels present an engine of tourism development. Their standard and orientation towards specific target groups of customers determine the strength of tourism offer. In addition, they contribute to the agricultural development, too, because they are the great buyers of agricultural products. According to official data, the existing potentials of Serbian tourism have been insufficiently valorised and Serbian hotels are in pretty poor condition- compared to international standards. Taking these facts into consideration, we can raise a question whether the key problems of Serbian hotels lie exclusively in inadequate accommodation capacities, or perhaps that there is a lack of customer- oriented business philosophy. Also the question is to what extent the legal regulations contribute to the protection of customer rights and their satisfaction. Therefore, the purpose of this paper is to ascertain the level of customer orientation in Serbian hotels, so as to find out whether members of hotel staff are acquainted with the notion of customer orientation and determine the degree to which this approach has been applied in practice. Conclusions and recommendations for improvement of competitiveness of hotels in Serbia are derived on the basis of research conducted by interviewing the employees of a sample of hotels in Serbia.